2022
DOI: 10.1002/ctm2.694
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing technologies and applications: A brief overview

Abstract: Single‐cell RNA sequencing (scRNA‐seq) technology has become the state‐of‐the‐art approach for unravelling the heterogeneity and complexity of RNA transcripts within individual cells, as well as revealing the composition of different cell types and functions within highly organized tissues/organs/organisms. Since its first discovery in 2009, studies based on scRNA‐seq provide massive information across different fields making exciting new discoveries in better understanding the composition and interaction of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
204
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(306 citation statements)
references
References 207 publications
0
204
0
11
Order By: Relevance
“…Lastly, there are also techniques based on the principle of combinatorial indexing for barcode attachment [ 80 , 81 , 82 ]. A more thorough review and benchmarking of the many existing scRNA-seq methods have been reported by others [ 83 , 84 ]. These four types of scRNA-seq assays have all been used for studying MKs and their precursors in humans.…”
Section: Single-cell Transcriptomics Of Healthy Megakaryocytesmentioning
confidence: 99%
“…Lastly, there are also techniques based on the principle of combinatorial indexing for barcode attachment [ 80 , 81 , 82 ]. A more thorough review and benchmarking of the many existing scRNA-seq methods have been reported by others [ 83 , 84 ]. These four types of scRNA-seq assays have all been used for studying MKs and their precursors in humans.…”
Section: Single-cell Transcriptomics Of Healthy Megakaryocytesmentioning
confidence: 99%
“…Single cell RNA-seq (scRNA-seq) technology enables high throughput transcriptomic profiling of individual cells. First published in 2009, scRNA-seq has evolved massively over the past decade, giving rise to more streamlined and affordable scRNA-seq technologies such as microfluidic-based microwell-based, droplet-based and in situ barcoding [ 127 , 128 ]. These methods, however, require cells or nuclei to be in suspension, leading to the loss of information on the spatial contexture.…”
Section: Emergence Of Single-cell Technologiesmentioning
confidence: 99%
“…New types of cells and more clearly defined cellular subsets have been identified using cluster algorithms and unbiased dimension reduction. Single-cell RNA bioinformatic methods have been described in detail previously [ 13 , 14 , 15 , 16 ].…”
Section: Single-cell Omics Technologiesmentioning
confidence: 99%